Psychological Status among the Medical Interns in Jeddah Hospitals during COVID-19 - Hasan, Abd Alhadi Ibrahim; Alfagieh, Arwa Mohammed; Alghamdi, Meshal Fahad; Abumohssin, Abdulelah Ghassan Ibrahiem; Balubaid, Rafal Nasser Saeed; Alsowaidi, Abrar Mohammed Saeed (British Journal of Healthcare and Medical Research, 2023)
Introduction: Coronavirus (COVID-19) is a highly transmissible virus that causes severe respiratory illness, by March 12, 2020 the virus was declared as a pandemic by the WHO, the first case in Saudi Arabia was announced at 02 march 2020. This outbreak was associated with a high public anxiety, Due to their long working hours and a higher risk of infection, medical interns could face some psychological problems. Our aim is to investigate the psychological status of medical interns during coronavirus (COVID-19) outbreak in Jeddah, Saudi Arabia. Methodology: This Cross-sectional study was conducted in the period between July-August 2020 in Jeddah, Saudi Arabia. Data was collected using an online questionnaire distributed. A total number of 319 participants answered the online survey, but a total of 270 responses were included in this study. We used latest version of SPSS for the analysis. Results: In this study IES-R Overall showed that PTSD is a clinical concern, all other averages of DASS and IES-R subscales were normal. Females were significant IES-R overall and IES-R intrusion. In addition, participant above the age of 25 had a significant correlation with all DASS, IES-R and IES-R Overall. Private universities had significance with anxiety, avoidance, intrusion, hyperarousal, and IES-R Overall Conclusion: In our study we found that factors exacerbating psychological distress were, Gender (Females), Age > 25 years, graduating from Private universities. Both marital status and internship experience had no significant relation.